PENGARUH ARUS KAS DAN PERPUTARAN PIUTANG TERHADAP LIKUIDITAS PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Wihelmina Indut; Herly M. Oematan; Yohanes Demu (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2021)
This study aims to determine the effect of cash flow and receivables turnover either partially or simultaneously on the liquidity of food and beverage companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This type of research is quantitative research. The data used in this research is secondary data. The population in this study was 26 Food and Beverage companies listed on the Indonesia Stock Exchange. Sampling using purposive sampling, and the sample was obtained for this study as many as one third of food and beverage In Indonesia Stock Exchange period 2016 -2020. Data collection techniques in this research are literature study and documentation. The data analysis technique used in this study used multiple linear regression analysis, classical assumption test, and hypothesis testing. The results of this study are partially Cash Flow and Receivables Turnover have an effect on the liquidity of Food and Beverage Companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Simultaneously, Cash Flow and Accounts Receivable Turnover affect the Liquidity of Food and Beverage Companies listed on the Indonesia Stock Exchange for the 2016-2020 period.